Occurrence of natural radioactivity and corresponding health risk in groundwater with an elevated radiation background in Juban District, Yemen - Abdurabu, W. A. (Springer Verlag, 2016)
This study aims to investigate the occurrence of natural radiation in groundwater with an elevated background level in Juban District, Yemen, and to assess the corresponding health risk. The mean concentrations of U, Th, and K in groundwater were 11.25, 0.15, and 17.35 mg l-1, respectively. The mean activity concentrations of 226Ra, 228Ra, and 40K were 94, 216, and 3306 mBq l-1, respectively. 65 % of the groundwater samples were above the WHO guidance level for 228Ra in water. The maximum concentrations of 226Ra, Th, and 228Ra were found around the fault zones in the basement aquifer while the concentrations of U increase down-gradient of Juan District. The principal factors controlling the occurrence and concentrations of radionuclides are aquifer type, leaching behaviour, characteristics of fracture systems, salinity, and water flow path. The annual effective doses due to ingestion of the water were estimated for infant and adult groups. The mean annual effective dose for infants was 1.97 mSv year-1 which is almost twenty times the WHO guideline level for drinking water. The ingestion dose deduced for adults and infants is dominated by 228Ra, where the average contribution from 228Ra in infants amounted to 90 % and in adults 76 %.